RURAL BANK PROFITABILITY AND ITS DETERMINANTS: THE PRACTISE OF WEST JAVA’S RURAL BANKS IN INDONESIA DURING THE YEARS OF 2012-2016 (The Indonesian Journal of Business Administration, 2020)
This thesis aims to find out the factors that influence or determine the profitability of rural banks in West Java Province. This research is based on a condition that Rural banks in Indonesia generally experience unfavourable conditions given the high level of competition experienced by Rural banks themselves, coupled with competition with Commercial banks, where Commercial banks also enter the market that has been worked on by Rural banks, namely micro and small segments. In addition there was a significant development of Financial Technology (Fintech) with a concentration on the micro and small business market as well which eventually eroded the rural banks market share. In addition, the era of the low interest rate regime during the 2012-2016 period has led many Rural banks customers to move mainly to Commercial banks that are active in lending with the subsidy scheme, namely the People's Business Credit (KUR). This made many Rural banks unable to compete with them, which in turn resulted in many Rural banks being closed (bankrupt) during this period. However, in that period there were Rural banks that survived by showing high profitability performance. This study aimed to explore the factors that influenced the success of Rural banks that were still sustainable in that period.This study uses data from Rural banks in West Java Province which is under the supervision of regional office 02 West Java, Indonesia with a number of Rural Banks included in the study is as much as 212 banks. The selection of West Java as the Province to be analysed considering the population in West Java is the largest in all of Indonesia with the number of Rural banks are the second largest after East Java Province. The research method used is a quantitative method using panel data regression as the main analytical tools.The results showed that Return on Assets (ROA) reached an average of 2.44%, Capital Adequacy Ratio (CAR) achieved an average of 33.54%, Non-Performing Loans (NPL) reached an average of 11.57%, Operating Cost to Operating Revenue (OC_OR) reached an average of 94.72%, and Loan to Deposit Ratio (LDR) reached 81.79%. The Inferential statistical results show that the Natural Logarithm of Total Assets (LNTA), CAR and LDR have positive and significant effects on profitability, meanwhile NPL and OC_OR have negative and significant influences on the profitability.Based on the FGLS regression and Fixed Effects models, it is shown that in terms of order of urgency of each variable, it is proven that OC_OR is the most important variable that needs to be considered by bank managers so that banks are more profitable. After OC_OR, the second most important variable is CAR, then followed by LDR, NPL, and finally LNTA.As the problem solving model for the Management of Rural banks, it is advised that in regards to enhance the profitability of the Rural banks, the management of Rural banks should be aware of reducing Operational cost portion as well as enhancing the Capital Adequacy into the optimal number, and following by extending LDR into the ideal ratio, reducing the problem loans and enlarging the asset to improve the banks’ profitability. Keywords: Rural banks, Profitability, Panel data regression, Operational costs, Capital Adequacy